Severe gastrointestinal bleeding due to jejunal diverticulosis - Gateño Yaffe, Nisso; Lucinschi, Alicia; Guzmán, Prudencio (Cirugía del Uruguay, 1976)
A case of severe digestive hemorrhage by complicated jejunal diverticulitis is presented. The infrequency of this entity, and its complications, are remarked. Sorne considerations are maéie about the etiology, usefulness of explorative enterotomy in order to locate the sourc e of bleeding.